PERMASALAHAN PERAN DAN FUNGSI BADAN PERMUSYAWARATAN DESA (STUDI KASUS DI DESA POCO RI’I, KECAMATAN BORONG, KABUPATEN MANGGARAI TIMUR, FLORES, PROVINSI NUSA TENGGARA TIMUR) - Jeliha, Krista; Nugroho, Wahyu Budi; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
The research aims to analyze and explain the existence of the Village Consultative Body in carrying out its main duties and functions as a government organizer in Poco Ri'i Village, East Manggarai Regency. The Village Consultative Body is an interesting research object to study from a sociological perspective. This study uses Adam Smith's theory of bureaucratic pathology, analyzing the role and function of the Village Consultative Body which affects the sustainability of rural community democracy. Using a qualitative approach with this type of descriptive-explanatory research. The data collection method is applied to support the success, the accuracy of the research data. Through a series of applied methods, JURNAthe results of research that reveal the problems, roles and functions of the Village Consultative Body in Poco Ri'i Village, East Manggarai Regency, understand the important role of the Poco Ri'i Village Consultative Body. Keywods: Problems, Roles and Functions, Village Consultative Body.